Respostas
respondido por:
2
3x^2+4=13x
3x^2-13x+4=0
delta=b^2-4ac
delta=(-13)^2-4.3.4
delta=169-48
delta=121
x=-b-/+ raiz de delta/2a
x=-(-13)-11/2.3
x=13-11/6
x=2/6 (:2)
x=1/3
x=-(-13)+11/2.3
x=13+11/6
x=24/6
x=4
3x^2-13x+4=0
delta=b^2-4ac
delta=(-13)^2-4.3.4
delta=169-48
delta=121
x=-b-/+ raiz de delta/2a
x=-(-13)-11/2.3
x=13-11/6
x=2/6 (:2)
x=1/3
x=-(-13)+11/2.3
x=13+11/6
x=24/6
x=4
respondido por:
1
Primeiro vamos igualar essa equação a zero:
Depois, encontrar o Delta, sendo:
Agora, resolveremos por Bháskara:
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás